METHODOLOGY FOR STUDYING THE FIRE PROTECTION ABILITY OF A FIRE PROTECTION COATING BASED ON POLYSILOXANE AND OXIDES OF ALUMINIUM, TITANIUM, AND CHROMIUM FOR STEEL BUILDING STRUCTURES - Veselivskyi, R.; Yakovchuk, R.; Smoliak, D.; Petrovskyi, V. (Municipal economy of cities. Series: «Economy science», 2024)
Fires and their negative consequences are a significant problem today. The final report of the World Fire Statistics Centre in 2023 shows that an average of 3.7 million fires occurred annually between 1993 and 2021. The fire resistance of building structures has paramount importance and influence on the development and spread of fires in buildings and structures, which needs consideration at the design stage. Particular attention should be paid to metal structures when used in construction since their fire resistance limit is about 15 minutes, depending on the profile and cross-section of the structure, and this, in turn, limits their use in buildings and structures where the fire resistance class of structures is REI 15. A way to increase the fire resistance class of a steel building structure is its fire protection implemented using dedicated means that protect the steel structure from the effects of high fire temperatures. The study aims to develop a methodology and determine the heating time of prototypes of steel plates with a fire-retardant coating based on polysiloxane and oxides of aluminium, titanium, and chromium to a critical temperature depending on the coating thickness (0.3, 0.45, 0.6, 0.8 mm) and the thickness of the steel plate (0.3, 0.5, 0.8 cm). To determine the fire protection capacity of the developed fireproof coating, we used the method regulated by clause 7.4 of DSTU-N-P B V.1.1-29:2010 ‘Fireproof treatment of building structures. General requirements and control methods’. The authors have developed a methodology for conducting experimental studies of the effectiveness of fire protection coatings using an installation for determining the fire protection capacity (effectiveness) of fire protection coatings, the principle of which is to heat the interior of the installation chamber using electric heating elements. The heating time of the prototypes of steel plates with the developed fire protection coating to the critical temperature was determined, depending on the coating thickness and the thickness of the steel plate. We found that the extreme temperature in a steel plate with a thickness of 0.3 cm is reached at 23, 34, and 46 minutes with a coating thickness of 0.3, 0.45, and 0.6 mm, respectively. Experimental studies of steel plates with thicknesses of 0.5 and 0.8 cm have shown that with an increase in plate thickness at the same values of the thickness of the fire protection coating, the time to reach the extreme temperature increases by about 1 minute. At a coating thickness of 0.8 mm, for steel plates with thicknesses of 0.3 and 0.8 cm, the temperature on the unheated surface of the prototype did not reach the extreme value.Given the results obtained, it will be relevant to solve the inverse problem of thermal conductivity to determine the thermal and physical characteristics of the coating based on numerical data from experimental studies.